Estudo do desgaste erosivo do aço inoxidável austenítico AISI 201: uma comparação com os aços AISI 304 e AISI 410 - Ana Paula Marques de Oliveira (2017)
Erosive wear is caused by hard particles striking the surface, either carried by a gas stream or a flowing liquid. It is a phenomenon very common in mining and agroindustry processes where transfer materials points (transfer chutes)are present. Several factors and parameters ofthe tribological system influence the erosion, so mechanical and metallurgical materials characteristics are fundamental for this analysis. The objective of the work is to study the stainless steel structures influence on the erosion resistance. Three stainless steels werechosen: AISI 410, AISI 304 and AISI 201, the latter being the research main focus, since it is a less studied material, but with a high potential for future applications and a lower production cost. The influence of the cold rolling treatment of the AISI 201 on its erosive wear was also evaluated. The tests were performed with incidence angles of 20° and 90° and the eroded samples were characterized by metallographic, microhardness and profilometry tests. Besides, the as-received stainless steels were characterized through chemical, metallographic and mechanical analyzes. All studied materials presented erosive wear by plastic deformation, with a greater erosive wear resistance for the AISI 201 steel. Its high ductility, good hardening rate and great tendency to form martensite by deformation were fundamental for this behavior. Erosion rates, ratio of mass of material removed per mass of erosive particles that collide with a surface in g/g for incidence angle of 20° were 1.2.10-6 for the AISI 201, 1.8.10-6 for the AISI 304 and 5.7. 10-6 for AISI 410, and for incidence angle of 90° were 0.011.10-6 for AISI 20, 0.110.10-6 for AISI 304 and 3,264.10-6 for AISI 410. In this way, the AISI 201 steel appeared as a promising material for applications in equipment that undergo erosive wear. However, the previous hardening of the AISI 201, with a reduction of 30% and 55%, was not favorable in this process